2020
DOI: 10.1111/and.13606
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effect of clove essential oil and its major component, eugenol, on erectile function in diabetic rats

Abstract: Diabetic men are at a higher risk of erectile dysfunction (ED). A tropical plant, clove (Syn. Eugenia caryophyllata, Caryophyllus aromaticus L., Syzygium aromaticum (L.) Merr. & L.M. Perry) from the Myrtaceae family has displayed aphrodisiac activity. The present research aimed to investigate the impacts of clove essential oil (CEO) and the ingredient of CEO, eugenol (E) on ED in diabetic rats. We divided Sprague‐Dawley rats into control and diabetic groups. Erectile function was evaluated before and after CEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Microemulsions, in general, have a penetration-enhancing ability owing to their oily nature and small droplet size (8,10). For the formulation in this study, there is an additional enhancement of sexual activity brought about by clove oil, which can help to delay premature ejaculation (9,12).…”
Section: Resultsmentioning
confidence: 99%
“…Microemulsions, in general, have a penetration-enhancing ability owing to their oily nature and small droplet size (8,10). For the formulation in this study, there is an additional enhancement of sexual activity brought about by clove oil, which can help to delay premature ejaculation (9,12).…”
Section: Resultsmentioning
confidence: 99%
“…Spectral analysis of essential oils from S. aromaticum revealed several beneficial bioactive compounds, including eugenol, β-caryophyllene, vanillin, crategolic acid (maslinic acid), kaempferol, rhamnetin, eugenitin, eugenin, ellagic acid, gallic acid, biflorin, myricetin, campesterol, stigmasterol, oleanolic acid, quercetin, carvacrol, α-pinene, limonene, p-cymene, 1,8-cineole, phenethyl alcohol, benzyl acetate, methyl chavicol, α-terpineol, linalyl acetate, and nerol. 216,217 Of these bioactive, eugenol is the most predominant, with a relative abundance of 90.45% in S. aromaticum . In collagen-induced arthritis (CIA) model to investigate the potential role of eugenol in the management of human arthritis, eugenol (100 μg) suppressed mononuclear cell infiltration into the knee joints of arthritic mice.…”
Section: Indigenous Nigerian Medicinal Plants Whose Bioactive Compoun...mentioning
confidence: 99%
“…In an experiment, it has been showed that Sesame oil with 20% of feed intake has showed a protective effect in the brain to enhance the immunity of rats against the oxidative stress [39]. It has been identified that Clove oil has improved the immune response and activated relaxation signal pathway for more immunity enhancement in rats[42]. It was also observed that dietary supplements with 0.5%, 1% and 1.5% of clove oil were useful for growth, disease resistance and strong immunity in Nile tilapia[43].…”
mentioning
confidence: 99%